Electrochemical Properties of Fe2O3 Electrode in Alkaline Solution Containing K2S Additive - Thi Hang, Bui (VNU Journal of Science: Mathematics - Physics; Vol 34 No 2DO - 10.25073/2588-1124/vnumap.4274, 2018)
To find the suitable materials for Fe/air battery anode, in this study Fe 2 O 3 electrodes were prepared using Fe 2 O 3 nanoparticles. The size and morphology of Fe 2 O 3 material were observed by scanning electron microscope (SEM). The electrochemical properties of the Fe 2 O 3 electrode in alkaline solution were investigated by using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The effects of K 2 S additive in electrolyte solution on the electrochemical characteristics of Fe 2 O 3 electrodes were also investigated. The obtained results show that the additive strongly affected on the impedance, redox reaction rate and cyclability of Fe 2 O 3 electrode Keywords: Fe 2 O 3 nanoparticles, Fe 2 O 3 electrode, K 2 S additive, Fe-air battery. References [1] A. K. Manohar, S. Malkhandi, B.Yang, C. Yang, G.K.S. Prakash, and S.R. Narayanan, A High Performance Rechargeable Iron Electrode for Large Scale Battery Based Energy Storage, Journal of The Electrochemical Society 159 (2012) A1209. [2] A. Inoishi, Y. W. Ju, S. Ida, T. Ishihara, Fe-air rechargeable battery using oxide ion conducting electrolyte of Y2O3 stabilized ZrO2, Journal of Power Sources 229 (2013) 12. [3] C. Kao, K. Chou, Iron/carbon-black composite nanoparticles as an iron electrode material in a paste type rechargeable alkaline battery, Journal of Power Sources 195 (2010) 2399. [4] B. Cui, H. Xin, S. Liu, X. Liu, Y. Hao, Q. Guo, and S. Licht, Improved Cycle Iron Molten Air Battery Performance Using a Robust Fin Air Electrode, Journal of The Electrochemical Society 164 (2017) A88. [5] A. Paulraj, Y. Kiros, B. Skarman, and H. Vidarsson, Core/Shell Structure Nano-Iron/Iron Carbide Electrodes for Rechargeable Alkaline Iron Batteries, Journal of The Electrochemical Society 164 (2017) A1665. [6] U. S. Department of Energy, APRA-Efunding announcement, GridscaleRampable Intermittently Dispatchable Storage, 2010. [7] S. Narayanan, G. S. Prakash, A. Manohar, B. Yang, S. Malkhandi, A. Kindler, Materials Challenges and Technical Approaches for Realizing Inexpensive and Robust Iron-Air Batteries for Large-Scale Energy Storage,Solid State Ionics 216 (2012) 105. [8] T.S. Balasubramanian, A.K. Shukla, Effect of metal-sulfide additives on charge/discharge reactions of the alkaline iron electrode, J. Power Sources 41 (1993) 99. [9] J. Cerny, J. Jindra, K. Micka, Comparative study of porous iron electrodes, J. Power Sources 45 (1993) 267. [10] P. Periasamy, B.R. Babu, S.V. Iyer, Performance Characterization of Sintered Iron Electrodes in Nickel/Iron Alkaline Batteries, J. Power Sources 62 (1996) 9. [11] C.A. Caldas, M.C. Lopes, I.A. Carlos, The role of FeS and (NH4)2CO3 additives on the pressed type Fe electrode, J. Power Sources 74 (1998) 108. [12] C.A.C. Souza, I.A. Carlos, M.C. Lopes, G.A. Finazzi, M.R.H. de Almeida, Short communication Self-discharge of Fe–Ni alkaline batteries, J. Power Sources 132 (2004) 288. [13] A. Manohar, C.Yang, S. Malkhandi, G.K.S. Prakash, and S.R.Narayanan, Enhancing the Performance of the Rechargeable Iron Electrode in Alkaline Batteries with Bismuth Oxide and Iron Sulﬁde Additives”, Journal of The Electrochemical Society 160 (2013) A2078. [14] J. Cerny, K. Micka, Voltammetric study of an iron electrode in alkaline electrolytes, J. Power Sources 25 (1989) 111. [15] P. Periasamy, B.R. Babu, S.V. Iyer, Electrochemical behaviour of Teflon-bonded iron oxide electrodes in alkaline solutions, J. Power Sources 63 (1996) 79. [16] B. T. Hang, T. Watanabe, M. Egashira, I. Watanabe, S. Okada, J. Yamaki, The effect of additives on the electrochemical properties of Fe/C composite for Fe/air battery anode, J. Power Sources 155 (2006) 461. [17] A. K. Manohar, C. Yang, and S.R. Narayanan, The Role of Sulﬁde Additives in Achieving Long Cycle Life Rechargeable Iron Electrodes in Alkaline Batteries, Journal of The Electrochemical Society, 162 (2015) A1864. [18] K. Micka, Z. Zabransky, Study of iron oxide electrodes in an alkaline electrolyte, J. Power Sources 19 (1987) 315. [19] M. Jayalakshmi, B.N. Begumi, V.R. Chidambaram, R. Sabapathi, V.S. Muralidharan, Role of activation on the performance of the iron negative electrode in nickel/iron cells, J. Power Sources 39 (1992) 113. [20] B.T. Hang, M. Egashira, I. Watanabe, S. Okada, J. Yamaki, S. Yoon, I. Mochida, The effect of carbon species on the properties of Fe/C composite for metal-air battery anode, J. Power Sources 143 (2005) 256. [21] B. T. Hang, T. Watanabe, M.Egashira, I. Watanabe,S. Okada, J.Yamaki, The Effect of Additives on the Electrochemical Properties of Fe/C Composite for Fe/Air Battery Anode, J. Power Sources 155 (2006) 461. [22] D. W. Shoesmith, P. Taylor, M. G. Bailey and B. Ikeda,Electrochemical behaviour of iron in alkaline solutions,Electrochim. Acta, 23 (1978), 903. [23] G. P. Kalaignan, V. S. Muralidharan and K. I. Vasu, Triangular potential sweepvoltammetricstudy of porous iron electrodes in alkali solutions,J. Appl. Electrochem., 17 (1987), 1083.